2018
DOI: 10.1177/0971355718810296
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Capabilities and Entrepreneurial Ecosystems: The Micro-Foundations of Regional Entrepreneurship

Abstract: In pursuit of the beneficial outcomes of entrepreneurship, governments and regional development organisations enact policies to stimulate entrepreneurial activity. A growing focus of policymakers in emerging and developed economies is the promotion of entrepreneurial ecosystems: the interconnected system of forces that generate and sustain regional entrepreneurship. Despite intense interest in entrepreneurial ecosystems, the topic is under-theorised. Studies draw attention to the positive effects of entreprene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 100 publications
0
74
0
6
Order By: Relevance
“…Similarly to entrepreneurs and SMEs, the social aspects surrounding the work of IT professionals and socioeconomic support professionals interacting with other actors are also crucial to help connect their respective resources and expertise (Dyer and Kale, 2007). This explains why, from an ecosystemic perspective, actual inputs and requirements may sometimes differ from the current discourse about SMEs needing to engage in a 'Digital agenda' and rush to address the urgency of the 'Digital transformation' (Roundy and Fayard, 2018). They also distinguish these networks from another type of ecosystem called "multi-actor network" that includes "entrepreneurs and private investors, innovators who are outside of company pipelines, users/user communities, governmental bureaucrats/policy makers, and consortiums" (Tsujimoto et al (2018, p. 6).…”
Section: Value Cocreation For Digital Transformation In Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to entrepreneurs and SMEs, the social aspects surrounding the work of IT professionals and socioeconomic support professionals interacting with other actors are also crucial to help connect their respective resources and expertise (Dyer and Kale, 2007). This explains why, from an ecosystemic perspective, actual inputs and requirements may sometimes differ from the current discourse about SMEs needing to engage in a 'Digital agenda' and rush to address the urgency of the 'Digital transformation' (Roundy and Fayard, 2018). They also distinguish these networks from another type of ecosystem called "multi-actor network" that includes "entrepreneurs and private investors, innovators who are outside of company pipelines, users/user communities, governmental bureaucrats/policy makers, and consortiums" (Tsujimoto et al (2018, p. 6).…”
Section: Value Cocreation For Digital Transformation In Smesmentioning
confidence: 99%
“…In an actor-to-actor (A2A) orientation for value creation (Vargo and Lusch, 2011), or recently what has been named "entrepreneurial ecosystem" (Roundy and Fayard, 2018), offers a wide range of resources and services through IT professionals and various suppliers and professionals (e.g. service/multi-actor ecosystem).…”
Section: Making Sense Of Digital Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…A lthough the concept is not new, there is still a growing amount of literature on entrepreneurial ecosystems Ghio et al, 2019;Roundy, 2017;Roundy, Fayard, 2019]. The theoretic foundation of the entrepreneurial ecosystem (EE) concept is grounded in the literature on regional innovation systems, academic spin-offs, the triple helix model, and also in the literature on the interplay between institutional context and entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies of EEs in Boulder and Silicon Valley, USA (Kenney & Von Burg, ; Neck, Meyer, Cohen, & Corbett, ; Saxenian, ) and Victoria, Canada (Cohen, ) found that an EE's ability to promote and sustain entrepreneurial activity is improved by specific components, such as networks connecting entrepreneurs, cultures supportive of risk‐taking, early‐stage investment, success stories, local consumers, and support organizations (Isenberg, ; Theodoraki, Messeghem, & Rice, ). Ecosystem components create an environment that assists entrepreneurs and increases the likelihood of venture success (Roundy & Fayard, ). However, the mere presence of EE components is not indicative of a vibrant ecosystem (Breznitz & Taylor, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%